Landasan Pendidikan Adab Santri Di Pondok Pesantren Modern - Kamaludin, Kamaludin; Mujahidin, Endin; Andriani, Nesia (Ulumuna: Jurnal Studi Keilsman, 2023)
One of the processes of changing a person's attitude in self-maturity efforts which is carried out with full awareness with clear intentions is through education. To improve the standard of living, the process of an education can last as long as the spirit is still attached to the soul. The foundation of education, namely the foundation for education which is used as a tool for developing human resources, is also a foundation that becomes a principle in thinking about a stage of planning, implementation, and the results of the educational process. In this highly sophisticated era, immoral acts stalk the next generation of the nation caused by various aspects, the reduced character education or etiquette of students towards teachers given in class or at home is one of these aspects. Educational institutions, especially modern Islamic boarding schools, must be present to offer concrete solutions to every problem that exists in the world of education and as a model for implementing adab and akhlakul karimah, so that they are directed to always educate students with adab before educating them with knowledge, so that later they will come out as figures of the next generation. who know knowledge and people of knowledge, before they know science itself.